Bias in Hiring Applicants With Mental Illness and Criminal Justice Involvement: A Follow-Up Study With Employers - Batastini, Ashley B. (Criminal justice and behavior, 2017)
Negative employer perceptions of job candidates with psychiatric and criminal backgrounds is one factor contributing to high unemployment rates among these groups. The current study replicated and extended Batastini et al., which evaluated stigmatizing beliefs toward hypothetical job applicants who had a known psychiatric and/or criminal history or neither (i.e., healthy control), as well as the effectiveness of a brief training component to mitigate biased attitudes. However, the current study addressed two major limitations of the original study by (a) including participants (N = 259) who reported current, past, or expected hiring experience and (b) including employer benefits in the training component. Results were generally consistent with prior research suggesting that people with psychiatric and criminal histories experience greater stigma from employers; however, the brief educational training component demonstrated minimal impact on reducing negative attitudes regardless of the applicant’s identified psychiatric or criminal background.